Learning Curves in COVID-19: Student Strategies in the ‘new normal’? - Millar, Sarah-Kate; Spencer, Kirsten; Stewart, Tom; Dong, Meg (Frontiers in Education, 2021)
In New Zealand, similar to the rest of the world, the COVID-19 pandemic brought unprecedented disruption to higher education, with a rapid transition to mass online teaching. The 1st year (and 1st semester in particular) of any University degree presents unique challenges for students. Literature suggests these students have significant learning concerns as they adjust to University teaching and assessment requirements. These challenges may be exacerbated with the rapid introduction of online learning environments as they are increasingly disconnected from their peers, and, at a greater risk of struggling with web-based learning technologies. This study investigated online learning strategies employed by 1st year students and examined the association between these strategies and student achievement. The University’s learning management system (LMS; Blackboard) was used to collect data related to students’ engagement with online content. The number of times content was clicked was recorded each day for the student’s three courses. These data were collected over a nine-week period for all students (N = 170) enrolled in the 1st semester of their degree. This nine-week period spanned from the commencement of COVID-19 online learning to the week of final assessments. The relationship between assessment date and online engagement was investigated and linear mixed models were used to determine if engagement with online learning was associated with final course grades. The results suggested that students adopted a learning strategy that coordinated their online LMS engagement with course assessment due date. Students had a greater specific engagement with the LMS 388% (SD 58%) on the assessment due date and the day prior, than throughout the remainder of their course. A further trend was observed whereby when an assessment was due in one course the students engaged less in the two other courses. Finally, a clear relationship between student LMS engagement and student course grade existed. For every additional week of zero LMS engagement, the odds of a student achieving a grade lower than B were 2.0 times higher (95% CI: 1.55, 2.64; p < 0.001), regardless of the course. rest continued in file